Peningkatan Nilai Perusahaan: Peran Leverage, Ukuran Perusahaan, dan Profitabilitas - Sherla Wijaya; Khairudin Khairudin (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
This study aims to analyze and obtain evidence regarding the effect of leverage, company size, and probility on corporate value in manufacturing companies listed on the Indonesia Stock Exhange for the 2017-2019 period. In this study, there are 3 independent vaiables tested, namely Debt to Equity (DER), Indikator Size (LN), and Return On Asset (ROA). And there is 1 dependent variable, namely Price to Book Value (PBV). The numbers of sample used are 21 manufacturing companies sub sector consumer goods onthes Indonesia Stock Exchange (IDX), the sampling technique used was purpose sampling. The analysis method used is the panel data regression analysis method using the Fixed Effect Model.the research result prove that leverage has no effect on corporate value, company size has negatif effect on corporate value, and probility has a positif effect on corporate value.